COMPREHENSIVE REHABILITATION APPROACH FOR MEDIAN NERVE NEUROPATHY COMPLICATED BY CERVICAL RADICULOPATHY: CASE REPORT IN A YOUNG GAME - Yudiansyah, Anggi Gilang; Kurniawan, Shahdevi Nandar; Lestari, Dwi Indriani; Pringga, Gutama Arya (PERDOSNI (Perhimpunan Dokter Spesialis Neurologi Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Background: Median nerve neuropathy, particularly associated with repetitive strain activities such as gaming, is increasingly recognized in clinical practice. This condition often necessitates a multidisciplinary and holistic approach for effective management, aiming to prevent long-term complications and improve functional outcomes. Case: A 21-year-old male presented with progressive weakness, paresthesia, and atrophy in the first three digits of both hands, attributed to excessive gaming, exceeding 12 hours daily. Neurological examination revealed marked weakness in muscles innervated by the median nerve, and electromyography (EMG) confirmed bilateral median nerve compression, compounded by cervical radiculopathy at the C6-7-8-T1 levels. Discussion: This case underscores the necessity of evaluating both peripheral nerve pathology and potential cervical radiculopathy in patients with extensive upper limb use. Intensive gaming, characterized by poor ergonomic practices, can exacerbate nerve compression, leading to significant neuropathic changes. The implemented multidisciplinary rehabilitation approach involved patient education on ergonomic modifications, targeted physical therapy to strengthen affected muscle groups, and strategies to optimize posture and reduce repetitive strain. This comprehensive intervention aimed to alleviate symptoms, restore function, and prevent further deterioration. Conclusion: The case highlights the complexities involved in managing median nerve neuropathy exacerbated by cervical radiculopathy in individuals engaged in repetitive, high-intensity activities. A comprehensive, evidence-based rehabilitation strategy is crucial for achieving optimal recovery, minimizing recurrence, and enhancing the patient’s quality of life. Further research is warranted to explore the long-term efficacy of such interventions and to develop tailored rehabilitation protocols for similar cases in the gaming community.